Parallel reaction pathways accelerate folding of a guanine quadruplex. Issue 3 (19th January 2021) - Harkness, Robert W; Hennecker, Christopher; Grün, J Tassilo; Blümler, Anja; Heckel, Alexander; Schwalbe, Harald; Mittermaier, Anthony K
Abstract: G-quadruplexes (G4s) are four-stranded, guanine-rich nucleic acid structures that can influence a variety of biological processes such as the transcription and translation of genes and DNA replication. In many cases, a single G4-forming nucleic acid sequence can adopt multiple different folded conformations that interconvert on biologically relevant timescales, entropically stabilizing the folded state. The coexistence of different folded conformations also suggests that there are multiple pathways leading from the unfolded to the folded state ensembles, potentially modulating the folding rate and biological activity. We have developed an experimental method for quantifying the contributions of individual pathways to the folding of conformationally heterogeneous G4s that is based on mutagenesis, thermal hysteresis kinetic experiments and global analysis, and validated our results using photocaged kinetic NMR experiments. We studied the regulatory Pu22 G4 from the c-myc oncogene promoter, which adopts at least four distinct folded isomers. We found that the presence of four parallel pathways leads to a 2.5-fold acceleration in folding; that is, the effective folding rate from the unfolded to folded ensembles is 2.5 times as large as the rate constant for the fastest individual pathway. Since many G4 sequences can adopt many more than four isomers, folding accelerations of more than an order of magnitude are possible via this mechanism.